Implementation of HIV and AIDS Management Policies in the City of Bandung - Hadi Prabowo; Ismail; Agus Fatoni (GoAcademica Research & Publishing, 2020)
Patients with HIV and AIDS in Bandung are problems that need treatment so that the number of people with HIV and AIDS decreases. This study aims to find out how the implementation of HIV and AIDS prevention policies in the city of Bandung and the driving and inhibiting factors by using the theory of Van Metter and Van Horn policy implementation. This study uses qualitative methods with a purposive sampling technique in determining informants and uses triangulation techniques in data analysis. The results of the study revealed that the implementation of HIV and AIDS prevention policies in the city of Bandung is still not going well because of the factors that have not been externally driven by a boost program, lack of public understanding and the absence of HIV AIDS drugs to cure the disease completely.